Main Philosophical Methodologies in the Economic Science - Prodanov, Vasil (Research Papers, 2017)
The main goal of the study is to reveal the parallel and the relationships in development of the mainstream trends in philosophy and methodology of science, methodology of economics and the changes in the economic reality. Through theoretical and comparative analysis, it is drawn a conclusion that the classical rationalist philosophical methodology of the European Enlightenment, the first and second positivism, neoposiitvism, postpositivist philosophy are methodological basis of each of the successive mainstream theoretical models of economic thinking in the developed capitalist countries from Adam Smith until now.
Keywords: Economics; Rationalism; Postpositivism; Classical political economy; Empirism; Methodology; Positivism; Method dispute